Foreign student´s memorable tourism experiences about Porto city - Pinto, Catarina (2022)
The identification of the dimensions that impact on the creation of memorable tourism experiences is a subject of the utmost importance, so that the touristic offering can be adjusted to the needs of the visitants. This research main goal is to identifying the dimensions of the memorable tourism experiences of the international students of the Instituto Politécnico de Bragança (IPB) that visit the city of Porto. It will allow an analysis on how the visitors create their memorable tourism experiences. An online inquiry was applied, structured in tree parts in order to answer to three specific goals of the research: i) analyse the profile of the international students of the IPB; ii) identify the dimensions of the memorable tourism experiences of the international students of the IPB; iii) analyse the behaviour of the international students of the IPB. The instrument of data collection was made available in two languages, Portuguese and English, and it was applied during the months of December 2020 and January 2021. Seven dimensions were evaluated (hedonism; renovation; novelty; social interaction; knowledge; meaning; involvement) on a sevenpoint Likert agreement scale. The results revealed that the dimensions that contribute the most to the creation of memorable tourism experiences were hedonism, renovation, novelty and involvement. Examples of these dimensions are the image of the city, the attractions the city possesses, local residents, the fact that they feel well during the trip or the fact that they don't forget the experience they had.